Peran Orang Tua dalam Mengembangkan Kreativitas Anak Usia Dini pada Masa Pandemi Covid-19 - Malikatus Sholihah (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2021)
This research was conducted to find out how the role of parents in developing early childhood creativity during the COVID-19 pandemic. The research subjects were students of RA Hidayatul Islamiyah, parents, teachers, and principals. Research data were collected by several techniques, such as observation, interviews, and documentation. The triangulation technique is carried out by means of triangulation of techniques and sources, namely by re-checking the information from interviews with documentation and observations and matching from one informant to other informants. The results of research on the role of parents in developing children's creativity in cooking cakes in the midst of the covid-19 pandemic, show that there are parents who pay less attention to children's learning activities at home, but there are also parents who collaborate with teachers to direct children to study at home. The conclusion of this research is the role of parents who have high enthusiasm in developing children's learning creativity will have a good impact on children, especially during the current covid-19 pandemic, children really need the role of parents to develop children's creativity through cooking cakes taught at home.